Trends in Service Marketing Strategies for Enterprises - Li, Yueqing (International Journal of Global Economics and Management, 2024)
In the context of intensifying market competition and increasingly diversified customer demand, the marketing strategies for enterprise service are facing unprecedented challenges. This paper will delve into the current and future trends of marketing strategies for enterprise services, analyze the key factors influencing these trends, and propose corresponding marketing strategy recommendations. Through a review of relevant literature, empirical research, and case analysis, this paper aims to provide enterprises with targeted marketing strategy guidance to adapt to the ever-changing market environment.